Determinants of diaphragm inspiratory motion, diaphragm thickening, and its performance for predicting respiratory restrictive pattern in Duchenne muscular dystrophy. Issue 1 (25th October 2021) - Fayssoil, Abdallah; Nguyen, Lee S.; Stojkovic, Tanya; Prigent, Helene; Carlier, Robert; Amthor, Helge; Bergounioux, Jean; Zini, Justine; Damez‐Fontaine, Sebastien; Wahbi, Karim; Laforet, Pascal; Nicolas, Guillaume; et al.
Abstract: Introduction/Aims: Respiratory status is a key determinant of prognosis in patients with Duchenne muscular dystrophy (DMD). We aimed to evaluate the determinants of diaphragm ultrasound and its performance in predicting restrictive respiratory patterns in DMD. Methods: This was a retrospective study of DMD patients followed in our center and admitted for an annual checkup from 2015 to 2018. We included DMD patients who underwent diaphragm ultrasound and pulmonary functional tests. Results: This study included 74 patients with DMD. The right diaphragm thickening fraction (TF) was significantly associated with age ( P = .001), Walton score ( P = .012), inspiratory capacity (IC) ( P = .004), upright forced vital capacity (FVC) ( P < .0001), supine FVC ( P = .038), and maximal inspiratory pressure (MIP) ( P = .002). Right diaphragm excursion was significantly associated with age ( P < .0001), steroid use ( P = .008), history of spinal fusion ( P < .0001), body mass index (BMI) ( P = .002), Walton score ( P < .0001), IC ( P < .0001), upright FVC ( P < .0001), supine FVC ( P < .0001), and MIP ( P < .0001). A right diaphragm TF >28% and a right diaphragm excursion>25.4 mm were associated with an FVC >50% with, respectively, an area under the curve (AUC) of 0.95 ( P = .001) and 0.93 ( P < .001). A left diaphragm TF >26.8% and a left diaphragm excursion >21.5 mm were associated with an FVC >50% with, respectively, an AUC of 0.95 ( P = .011) and 0.97 ( P < .001). Discussion: Diaphragm excursion and diaphragm TF can predict restrictive pulmonary insufficiency in DMD.